The use of suction sampler in the study of the entomofauna in a citrus orchard - Chagas, Evandro Ferreira das; Neto, Sinval Silveira (Pesquisa Agropecuaria Brasileira, 2014)
This research on the entomofauna in a Citrus orchard in Piracicaba, SP, Brazil, was done with the intention to collect the smaller sized species and to analyse them faunistically. The colections were realized with a portable vacuum sampler model AS-ESALQ. Every week ten trees were selected at random and twenty sections were effected from each crown. At the family and species level the order Coleoptera was best represented. The faunistical indices showed that the species Aleurothrixus floccosus (Maskell, 1896) and Toxoptera citricidus (Kirk., 1907) have to be considered real insect pests of Citrus. The sampling method used showed to be valid for studying population dynamics of small sized insects.